À dissonância da razão: uma interpretação do sublime e da música na estética de Kant - Araújo, Ana Monique Moura de (2017)
We recognize the Kant‟s apology for the moralization of aesthetic culture and art, or of the ethics of aesthetics indoctrination. Herein, we show how music undergoes a process of valuation that runs from the aesthetics and stay on ethical and idiosyncratic Kant‟s criteria. The way that he approaches the music makes it, on the other hand, can be related to the sense of the aesthetic experience of terrifying sublime (grässiliche Erhabene), which is contrary to the moral sublime (moralische Erhabene) and is an aesthetic category addressed sparingly as the music in some of his writings. We join the music and the sublime, to evaluate the possibility of aesthetic experience whose morality in purity (Reinung) projection is nullity or impurity. We do not reject the subject of morality and aesthetics in a confluence. We approach the possibility of reinvention of the meaning of moral at the confluence the aesthetic. This means: without doctrine or imperative meaning. This does not abandon the crucial themes in Kant‟s ethics or aesthetics, however, only overcomes the ethical formalism to return to the aesthetic field. In this case, we will try to approach that aesthetic overlaps the ethical and show how such this work would be impossible without recurrence to the theme of the sublime and music in Kant‟s thought.